Structural and Digital Transformation of the Financial Industry: A Futuristic Approach for Sustainable and Green Digitalization - Fahad, Shah; Bulut, Mehmet (Muslim Business and Economics Review, 2024)
This study examines the structural and digital transformation within the financial industry, portraying the urging need for green sustainable digitalization within Industry 4.0. This study aims to explore the role of digital technologies, such as artificial intelligence (AI), big data analytics, and the Internet of Things (IoT), in promoting environmental sustainability in the financial sector. The study reviews the existing literature and the identified critical challenges and opportunities in sustainable digital transformation. It proposes pathways for leveraging digitalization to attain socio-environmental sustainability and green finance. Empirical evidence supports such analysis, finding positive impacts that digital finance brings to green technology innovation and carbon neutrality, emphasizing the synergy of digital development with sustainability goals. The study finds that policy and regulation will be critical in smoothing the transition and fostering diverse social and environmental implications of sustainable digital finance. In this context, the study brings a futuristic outlook on the way digital technologies are integrated within corporate strategies to be part of sustainable development.